Containing the first outbreak of COVID-19 in a healthcare setting in India: The sree chitra experience - Gurpreet Singh; G Srinivas; E K Jyothi; L K Gayatri; Rakhal Gaitonde; Biju Soman (Wolters Kluwer Medknow Publications, 2020)
The response to the first health worker case in India and novel strategies adopted in the context of evolving pandemic of COVID-19 is presented here. On the same day of confirmation, institutional COVID cell was established, and contact tracing was started. A total of 184 contacts were identified and quarantined. Hospital services were scaled down, and responsibilities were reassigned. In-house digital platforms were used for daily meetings, contact tracing, line listing, risk stratification, and research. Reverse transcription polymerase chain reaction-based severe acute respiratory syndrome-CoV2 testing facility was established in the institute. All high-risk contacts were given hydroxychloroquine prophylaxis. No secondary cases were found. Hospital preparedness, participatory decision-making through institutional COVID cell, optimal use of in-house digital platforms, and coordination with the state health department and national bodies, including Indian Council of Medical Research, were the supporting factors. Rapidly evolving guidelines, trepidation about the disease, logistic delays, and lack of support systems for people under quarantine were the challenges in the containment exercise.